2018
DOI: 10.1007/978-3-319-93698-7_21
|View full text |Cite
|
Sign up to set email alerts
|

Topological Street-Network Characterization Through Feature-Vector and Cluster Analysis

Abstract: Complex networks provide a means to describe cities through their street mesh, expressing characteristics that refer to the structure and organization of an urban zone. Although other studies have used complex networks to model street meshes, we observed a lack of methods to characterize the relationship between cities by using their topological features. Accordingly, this paper aims to describe interactions between cities by using vectors of topological features extracted from their street meshes represented … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…SNs also provide useful information that shapes commutes, travel behaviors, and location decisions of households and firms (Kang, 2017; Shatu and Yigitcanlar, 2018). Theoretically, an analysis of SNs requires measuring both topological and geometric characteristics (Spadon et al., 2018). The topological character explains the SNs’ connectivity, centrality, and clustering, whereas the geometric character describes SNs’ distances, areas, and densities (Boeing, 2018a).…”
Section: Literature Reviewmentioning
confidence: 99%
“…SNs also provide useful information that shapes commutes, travel behaviors, and location decisions of households and firms (Kang, 2017; Shatu and Yigitcanlar, 2018). Theoretically, an analysis of SNs requires measuring both topological and geometric characteristics (Spadon et al., 2018). The topological character explains the SNs’ connectivity, centrality, and clustering, whereas the geometric character describes SNs’ distances, areas, and densities (Boeing, 2018a).…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the urban agglomeration level, researchers have pointed out the lack of methods for characterizing the relationship between cities that use road network topological features [37]. As such, recent studies have explored whether cities that have similar street network topology properties share similar characteristics in their populations and economic development levels.…”
Section: Understanding the Relationship Between Street Network And Ementioning
confidence: 99%
“…As such, recent studies have explored whether cities that have similar street network topology properties share similar characteristics in their populations and economic development levels. For instance, Spadon, Gimenes, and Rodrigues classified 645 cities in the state of Sao Paulo, Brazil based on their street network features and found that the topological characteristics of urban streets could, at a large scale, indicate or even predict their demography [37]. Along similar lines, Lee and Jung analyzed the topological features of street networks using multi-centralities methods and classified a series of cities into several groups that share common meta-information based on centrality.…”
Section: Understanding the Relationship Between Street Network And Ementioning
confidence: 99%
See 2 more Smart Citations